Histopathological study of tapeworm infection in Ovis bharal (L.) from Solapur district (M.S) India - Humbe, Atul; Jadhav, Swati; Borde, S N; Chandanshive, S S (International Multidisciplinary Research Journal, 2011)
Histopathological study of cestode parasite has been studied to find the pathological changes and extent of damage of the intestinal layers of Ovis bharal (L.). The worm Stilesia shindei is having scolex with four suckers, which is large, rounded, which are used for attachment of worm to the intestine of host Ovis bharal (L). The heavy infection of Stilesia shindei damage the intestinal layers i.e. mucosa, submucosa, and lamina propria, submucosa with profuse infiltration of eosinophils, lymphocytes and the plasma cells. When host-parasites equilibrium is disturbed, serious disease in host is the consequence, resulting in depletion or weakening of host.